O latim no contexto letrado do Brasil Colonial - Binato, Cláudia Valéria Penavel [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
O Grupo de Pesquisa A Escrita no Brasil Colonial estuda, ao longo dos últimos dez anos, documentos literários e não literários no contexto lusitano e brasileiro dos séculos XVI ao XVIII. Há muitos registros de textos escritos em latim, nessa época, que dialogam com os problemas da terra, da literatura, da religião, das atividades artesanais e que foram produzidos tanto tanto em manifestações coletivas, como as academias histórico-literárias, quanto individualmente, por autores que optaram por expor suas idéias nesse idioma. Apresentaremos, neste texto, alguns letrados do Brasil Colonial que recorreram ao latim como expressão literária.

The Writing in Colonial Brazil Research Group has been studying both literary and non-literary documents for the past ten years. These documents were produced in the th in the Portuguese and Brazilian contexts of the XVIth and XVIIth centuries. Many of these texts are written in Latin, concerning subjects such as land, literature, religion, or kraftsmen activities. They have been produced both collectively in historic and literary Academies and by individual writers. In this lecture we intend to present some of those men of letters who have chosen the Latin language to express themselves.
Latin language in Colonial Brazil
Keywords: The Writing in Colonial Brazil; historic and literary Academies; Brazilian Latinity; Escrita no Brasil Colonial; Academias Histórico-literárias; Latinidade Brasileira